HUBUNGAN JUMLAH ANGGOTA KELUARGA, PENGETAHUAN GIZI IBU DAN TINGKAT KONSUMSI ENERGI DENGAN STATUS GIZI ANAK SEKOLAH DASAR - Purnamasari, Dyah Umiyarni; Dardjito, Endo; Kusnandar, Kusnandar (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2016)
ABSTRACTNutritional problems in school children need to be given serious attention. Impact of nutritional problems in school children can affect motor skills and academic achievement. The purpose of this study was to determine The Correlation of family members, maternal nutrition knowledge and level of energy consumption with nutritional status of elementary school children. Cross sectional study was conducted, the sample totaled 84 students. A total of 51.2% of families have a large number of members, as many as 65.5% of mothers have sufficient knowledge of nutrition, as many as 85.7% had levels less energy consumption and as much as 65.5% had normal nutritional status. The analysis was performed with Spearman Range test. There is a correlation between level of energy consumption and nutritional status (p = 0.001), there was no association of family members (p = 0.244), maternal nutrition knowledge (p = 0.115) with the nutritional status of school children. Suggestions to do school feeding to increase the level of consumption and nutritional status.Keywords: Elementary School Children, Nutritional status, Energy Consumption Kesmasindo, Volume 8, Nomor 2, Juli 2016, Hal. 44-51